Revascularization of Pancreatic Islet Allografts is Enhanced by α-1-Antitrypsin under Anti-Inflammatory Conditions. Issue 11 (November 2013) - Bellacen, Keren; Kalay, Noa; Ozeri, Eyal; Shahaf, Galit; Lewis, Eli C.
Pancreatic islets are a highly vascularized entity, and their transplantation into diabetic individuals requires optimal revascularization. In addition, β-cells in islets are extremely sensitive to inflammation. α-1-Antitrypsin (AAT), a circulating serine-protease inhibitor that is available for clinical use as an affinity-purified human product, has been shown to protect islets from graft failure in mouse transplantation models and to achieve readily vascularized islet grafts. AAT is known to induce vascular endothelial growth factor (VEGF) expression and release, as well as protect from proteolytic cleavage of VEGF by elastase, promote viability of endothelial cells, and enhance migration of myocytes. Our aim was to examine whether AAT enhances vasculogenesis toward islet grafts. We employed Matrigel-islet plugs as means to introduce islets in an explantable isolated compartment and examined vessel formation, vessel maturation, and inflammatory profile of explants 9 days after implantation. Also, we examined primary epithelial cell grafts that were prepared from lungs of mice that are transgenic for human AAT. In addition, aortic ring sprouting assay was performed, and HUVEC tube formation assays were studied in the presence of AAT. Our findings indicate that islet grafts exhibit mature vessels in the presence of AAT, as demonstrated by morphology, as well as expression of endothelial CD31, smooth muscle actin (SMA), and von Willebrand factor (vWF). Epithelial cells that express human AAT achieved a similar positive outcome. Aortic ring sprouting was enhanced in AAT-treated cultures and also in cultures that contained primary epithelial cells from human AAT transgenic animals in the absence of added AAT. According to the tube formation assay, HUVECs exhibited superior responses in the presence of AAT. We conclude that vasculogenesis toward islet grafts is enhanced in the presence of AAT. Together with the remarkable safety profile of AAT, the study supports its use in the relevant clinical setups.